The Role Of Stakeholders In Increasing Community Participation To Join As JKN-KIS Participants In Alam Barajo District In 2022 - Hopiyatun Aulia; Dwi Noerjoedianto; Rumita Ena Sari (Sean Institute, 2023)
The JKN-KIS program is a joint program, so the participation of all parties is needed, not only from the BPJS, the Government and participants who only need the benefits so that this program can run sustainably. The purpose of this study is to analyze the role of stakeholders in increasing community participation to join as JKN-KIS participants in Alam Barajo District in 2022. This research uses a qualitative research method with a phenomenological approach. Data were obtained from 11 informants by conducting in-depth interviews and observations in the Alam Barajo District, Jambi City. In this study, data analysis used the help of NVivo software and used triangulation of sources and methods to generalize the data that had been obtained. In increasing JKN-KIS participation in the aspect of the role of stakeholders in facilitators, coordinators, accelerators and evaluators that the implementation of the JKN-KIS program has been good, but stakeholders have carried out indirect socialization through intermediaries of other stakeholders, then coordination between cross-sectors has not been maximized, the community has not evenly felt the benefits of the JKN-KIS card and lack of understanding of the procedure for registering for the JKN-KIS program. So that in increasing public participation in JKN-KIS participation, the role of stakeholders from all parties is needed so that organizational goals can be achieved.